TRADITIONS AND INNOVATIONS IN THE INTERPRETATION OF LEGAL FACTS - Zavalniy, Andrey M.; Shapenko, Liudmyla O. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Purpose: theoretical development of the definition of a legal fact by considering traditional and modern approaches to understanding the concept and essence of this legal phenomenon. Nature, place and role of legal facts have been defined on the basis of the analysis of various scientific ideas about the evolution of legal facts. Methods: the use of the dialectical method of scientific knowledge and abstraction method allowed to analyze the content of the concept under study, to distinguish the main, most significant features and properties of legal facts that differentiate them from other social phenomena and distinguish them between legal ones. The functions of legal facts, their system-forming and regulatory potential for a legal system, as well as socio-economic significance in the process of transformation of social life have been defined with the help of the system-structural method and method of generalization. Results: the results of the scientific research prove the specificity of legal facts, which consists in the fact that they are phenomena of socio-legal reality and have material and normative components. Generalization of the features of a legal fact and research of its definition made it possible to determine a legal fact as an individual legal model of social circumstances, which is fixed in a certain legal way, serves as the basis for the emergence and functioning of legal relations, as well as the specification of the subjective rights and obligations of the participants in these relations. Simultaneous reflection of four planes – actual, personal, normative and communicative – reveals the content of legal facts more fully in this definition. Discussion: powerful development of the philosophy of law, the philosophical basis of various legal sciences and the directions of interdisciplinary research in the last decades requires further scientific understanding of legal facts using the philosophical approaches inherent in phenomenology, hermeneutics, praxeology and other philosophical systems. Thus, the necessity of working out of the corresponding methodological tools, which, taking into account the double legal and social nature of legal facts, would cover a considerable range of different scientific approaches, methods, methodological principles, etc., is actualized.